Vibration control of a flexible beam structure utilizing dynamic Green’s function - Bassam A. Albassam (Journal of King Saud University: Engineering Sciences)
The paper deals with designing a control force to create nodal point(s) having zero displacement and/or zero slope at selected locations in a harmonically excited vibrating structure. It is shown that the steady state vibrations at desired points can be eliminated using feedback control forces. These control forces are constructed from displacement and/or velocity measurements using sensors located either at the control force position or at some other location. A simple and exact closed form expression for the control force is derived using dynamic Green’s function. In a certain condition, this control force can be generated using passive elements such as springs and dampers. The design of robust feedback control with respect to excitation frequency variations is carried out and stability of the feedback control system is investigated. The effectiveness of the proposed method is demonstrated on various cases using Numerical examples.